2012
DOI: 10.3109/09553002.2013.741282
|View full text |Cite
|
Sign up to set email alerts
|

Influence of electromagnetic fields on reproductive system of male rats

Abstract: 10 GHz field has an injurious effect on fertility potential of male-exposed animals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 40 publications
1
28
0
2
Order By: Relevance
“…A second connection, to male infertility, is also hidden in the report. Two of the positive studies (53,54) are falsely stated in the Report as being on blood formation but what was actually being studied in both of these studies was testicular sperm formation. The positive study Liu et al (55) which shows genotoxicity in a spermatocyte cell line may also have implications regarding male infertility, because of the cell type being studied.…”
Section: Genotoxicity Of Non-thermal Microwave Exposures: Examples Ofmentioning
confidence: 99%
“…A second connection, to male infertility, is also hidden in the report. Two of the positive studies (53,54) are falsely stated in the Report as being on blood formation but what was actually being studied in both of these studies was testicular sperm formation. The positive study Liu et al (55) which shows genotoxicity in a spermatocyte cell line may also have implications regarding male infertility, because of the cell type being studied.…”
Section: Genotoxicity Of Non-thermal Microwave Exposures: Examples Ofmentioning
confidence: 99%
“…Exposure to mobile phone radiation 60 min/d for 3 mo significantly decrease the serum testosterone level of Wistar rats [28]. Exposed to 10 GHz microwave radiation for 2 h/day for 45 d significantly decreases the testosterone level of seventy day-old rats [30]. In spite of, exposure to electromagnetic field 1 800 and 900 MHz for 2 h continuously per day for 90 d [31] and exposure to 1 800 MHz GSM-like [32] caused an enhance in testosterone level.…”
Section: Discussionmentioning
confidence: 93%
“…Several studies have reported that EMF leads to interruption of spermatogenesis, impairment of sperm quality, degeneration of germinal epithelium cells, impaired testosterone levels, infertility, premature birth in rats and a decrease in testicular biopsy scores (Svedenstal and Johanson 1995, Dasdag et al 1999, Al-Akhras et al 2001, Ozguner et al 2005, Mailankot et al 2009, Li et al 2010, Kumar et al 2013. In contrast, however, other studies have reported that EMF has no effect on male fertility or else that the effect of EMF depends on intensity, length of exposure, wavelength and distance from EMF (Margonato et al 1995, Cecconi et al 2000, Dasdag et al 2003, Kim et al 2006, Çelik et al 2012, Gye and Park 2012.…”
Section: Discussionmentioning
confidence: 99%